Atypical Miller Fisher Syndrome with Anisocoria and Rapidly Fluctuating Pupillary Diameter. (24th August 2015) - Gupta, Garima; Liu, Antonio
Abstract : Miller Fisher syndrome is a variant of Guillain-Barre syndrome characterized by the classic triad of ophthalmoplegia, ataxia, and areflexia. Pupillary involvement is common in MFS and has been reported in 35–42% of MFS patients. Although case reports have discussed isolated ophthalmoplegia as a presentation of MFS, anisocoria and rapid fluctuation of pupillary diameter have not been reported in anti-GQ1b antibody positive individuals. Here we describe an individual who presented with diplopia and was found to have progressive internal and external ophthalmoplegia with frequent fluctuations in pupillary diameter and anisocoria. These exam findings are not commonly described even in atypical presentations of MFS. The onset of symptoms was preceded by an upper respiratory infection but no gastrointestinal symptoms. Imaging and CSF studies were unremarkable; however serum levels of immunoglobulin G anti-GQ1b antibody and anti-GAD antibody were elevated confirming the diagnosis of MFS. The patient was treated with IVIG and intravenous steroids with mild resolution of external ophthalmoplegia. He did not go on to develop more typical features of MFS such as ataxia or areflexia. This demonstrates that isolated external and internal ophthalmoparesis with rapidly fluctuating pupillary diameter and associated anisocoria can be the sole manifestation of atypical MFS.